A series of quaternary ammonium salt antibacterial agents synthesized and prepared for constructing and screening antibacterial coatings with biosafety on polypropylene - Wang, Leixiang; Nan, Shukai; Wang, Qiaozhi; Xu, Yinuo; Cui, Meng; Wang, Fenglai; Liu, Yaxuan; Hou, Guige; Liu, Zhonghao; Zhou, Wenjuan; Zhao, Yu-Qing (Frontiers in Microbiology, 2026)
Diseases caused by bacteria have become the world’s largest threat, and the treatment of bacterial infections urgently needs to be addressed. However, the abuse of antibiotics leads to superbugs, making bacterial infections more difficult to resolve. Therefore, there is an urgent need to develop new antibacterial agents. In this study, three antibacterial agents were synthesized. In vitro antibacterial experiments demonstrated that the antibacterial agent quaternized polyethyleneimine (QPEI) possessed favorable antibacterial activity and exhibited good antibacterial performance against a diverse array of bacteria and fungus, such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans. QPEI-C6 has an inhibitory concentration of 8 μg/mL against Staphylococcus aureus, 128 μg/mL against Escherichia coli, 16 μg/mL against Candida albicans, and 32 μg/mL against Pseudomonas aeruginosa. Furthermore, through antibacterial and cell biocompatibility experiments, it was shown that QPEI-C6 had good biocompatibility and excellent antibacterial performance within the concentration range of 8–128 μg/mL. The antibacterial agent QPEI-C6 combined with the natural polyphenol tannic acid (TA) was subsequently employed to modify the surface of polypropylene (PP) material, leading to outstanding bactericidal, anti-inflammatory, and antioxidant efficacies. The hemolysis rate of the final material group was 3.4%, and the in vitro cell survival rate was as high as 110%. The antibacterial rate against S. aureus reaches 99%. On the surface of the modified material, excessive reactive oxygen species (ROS) could be effectively eliminated, and the generation of oxidative stress was significantly mitigated. Anti-inflammatory experiments indicated that the coating substantially reduced the expression levels of TNF-α and IL-6 while promoting the release of IL-10. In this work, the cationic antibacterial agent QPEI was successfully synthesized, and the PP material was surface modified. A suite of materials with excellent antibacterial, antioxidant, and biocompatibility properties, which have positive and significant implications in the biomedical field, are presented in this work.